MENINGKATKAN KETERAMPILAN MENYIMAK MENGGUNAKAN MODEL KOOPERATIF TIPE THINK PAIR SHARE (TPS) SISWA KELAS IV SDN 76 TAROWANG: penelitian tindakan kelas pada siswa kelas IV SDN 76 Tarowang - Maelani vira dwiyana; Athiyyah_ Afiifah; Ernawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
: This study aims to improve the listening skills of fourth-grade students at SDN 76 Tarowang through the implementation of the cooperative learning model type Think Pair Share (TPS). This research is a classroom action research (CAR) conducted in two cycles, each consisting of four stages: planning, implementation, observation, and reflection. The subjects of this study were 8 fourth-grade students of SDN 76 Tarowang. The instruments used were observation sheets for teacher and student activities and learning outcome tests. The results showed that the application of the cooperative learning model type TPS could improve students' listening skills. This was evidenced by the increase in the average learning outcomes from 30% in the pre-cycle to 37.6% in the first cycle and significantly to 81.25% in the second cycle. Thus, the cooperative learning model type Think Pair Share (TPS) can be an effective alternative to improve the listening skills of elementary school students. Keywords: Listening skills, Cooperative model, Think Pair Share, Elementary school.